This is Our Brain - Hendrikse, Jeroen; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
Although many things can go wrong in the brain, this book also shows that our brain is strong. It highlights the key findings that can be seen on magnetic resonance imaging (MRI) and computed tomography (CT) scans, including those related to normal brain aging and common diseases such as brain infarcts, fractures of the skull as well as fractures and tumors of the vertebral column. It offers insights into brain MRI and CT scans, enabling readers to interpret the key findings.
CT and MRI scanners: the basics -- CT and MRI scans: different types of photos -- Brain anatomy -- White spots -- Brain shrinkage -- Silent infarcts -- Small old bleedings -- More space around the blood vessels -- Brain infarcts -- Brain bleedings.
Keywords: Popular works; Neurosciences; Human anatomy; Radiology; Medical physics; Radiation; Medicine; Health; Biomedical engineering; Popular Science; Popular Science in Medicine and Health; Biomedical engineering; Imaging / Radiology; Neurosciences; Medical and Radiation Physics; Anatomy